Hubungan antara faktor hygienie-motivator dengan kepuasan kerja pekerja bukan eksekutif CELCOM (M) SDN. BHD. Kawasan Timur, Kuching, Sarawak - Sharif, Bin Salleh (2001)
This research aims at identifying the relationship between two factors, hygiene and motivator based on Herzberg's Two-Factors Theory on job satisfaction level and related factors contributing to the job satisfaction and also to determine the relation between negative behaviors and job dissatisfaction among the non-executive staff in CELCOM (M) Sdn. Bhd. Eastern Zone, Kuching, Sarawak.